Calcaneal Fractures: A Soft Tissue Emergency - Tae-Seong Kim; Chang-Wug Oh; Joon-Woo Kim; Kyung-Hyun Park (Journal of Trauma and Injury)
Calcaneal fractures are quite often seen in patients with axial loading injury. In the tongue-type of calcaneusal fractures or tuberosity avulsion fractures, bone fragments are often superiorly and posteriorly displaced, because of the insertion of the Achilles tendon and pull of the gastroc-soleus complex. The Ddisplaced bone fragment compresses the soft tissues, leading tothat makes skin necrosis. To prevent further soft tissue injury, early recognition of the injury by the emergency physician and immediate orthopedic consultation is needed.